Green synthesis of nickel oxide nanoparticles using Lagerstroemia speciosa, Bombax ceiba, and Piper chaba extracts and evaluating their potential antioxidant, antidiabetic and antibacterial properties - Md. Harunur Roshid; Md. Shaha Alam; Kazi Abrar Ibn Amin; Farhana Khanam Ferdousi; Md. Hasanur Rahman; Shariful Islam (Heliyon)
This research involved the synthesis of nickel oxide nanoparticles using leaf extracts of Lagerstroemia speciosa, Bombax ceiba, and root extracts of Piper chaba. The nanoparticles underwent comprehensive analysis of their optical, structural, and morphological properties via methods like UV–visible Spectroscopy, Fourier Transform Infrared Spectroscopy, Scanning Electron Microscopy, Energy Dispersive X-ray, and X-ray Diffraction. Sharp absorption bands in between 323 and 342 nm in the UV–visible spectra indicated the successful formation of nanoparticles. The vibrational stretching mode of the Ni-O bond was confirmed through FTIR spectroscopy at ∼437 cm−1. XRD and SEM analyses were employed to determine the size and morphology of the synthesized NiO NPs. The scanning electron microscopy image demonstrated the spherical structure and average crystallite size from X-ray diffraction was found of about 40.17, 23.71 and 26.46 nm, respectively for Bombax ceiba, Lagerstroemia speciosa, and Piper chaba mediated NiO nanoparticles. Synthesized NiO nanoparticles exhibited significant α-amylase inhibition and antioxidant properties, specifically in their ability to scavenge DPPH free radicals. Furthermore, these nanoparticles demonstrated excellent antibacterial activity against the studied bacterial strains. Interestingly, Lagerstroemia speciosa mediated NiO nanoparticles displayed the highest biomedical properties. The IC50 values 45.23 and 21.03 μg/mL were found respectively for in vitro antioxidant and α-amylase inhibitory activities, while the maximum inhibition zone was measured 18.83 mm, 17.67 mm, and 22.10 mm for Escherichia coli, Saccharomyces aureus, and Pseudomonas aeruginosa, respectively at 250 μg/mL concentration for Lagerstroemia speciosa mediated NiO nanoparticles. Therefore, green synthesized NiO NPs especially nanoparticles hold great promise for various biomedical and biological applications and could potentially be explored for multifunctional uses in the future following a comprehensive in vivo study.